2020
DOI: 10.1177/2192568220944888
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Operating on Traumatic Spinal Injuries in Low-Middle Income Countries: A Preliminary Report From a Major East African Referral Center

Abstract: Study Design: Retrospective cost-effectiveness analysis. Objectives: While the incidence of traumatic spine injury (TSI) is high in low-middle income countries (LMICs), surgery is rarely possible due to cost-prohibitive implants. The objective of this study was to conduct a preliminary cost-effectiveness analysis of operative treatment of TSI patients in a LMIC setting. Methods: At a tertiary hospital in Tanzania from September 2016 to May 2019, a retrospective analysis was conducted to estimate the cost-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A total of 21 studies reported the mean cost of hospital acute care in 8 countries. The lowest costs were found in Nigeria, 41 Tanzania, 44 China, 39 and Taiwan 42 , 43 ($290 to $4,860). A study from Mexico reported the mean cost of acute care for complete cervical SCI to be $29,940.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A total of 21 studies reported the mean cost of hospital acute care in 8 countries. The lowest costs were found in Nigeria, 41 Tanzania, 44 China, 39 and Taiwan 42 , 43 ($290 to $4,860). A study from Mexico reported the mean cost of acute care for complete cervical SCI to be $29,940.…”
Section: Resultsmentioning
confidence: 95%
“…Most studies originated in North America (the U.S.: 15 studies, 15 - 29 and Canada: 7 30 - 36 ); and the rest were conducted in Australia, 37 , 38 China, 39 Mexico, 40 Nigeria, 41 Taiwan, 42 , 43 and Tanzania. 44 Sample sizes ranged from 34 to 15,510, and settings varied from hospital-based to nationwide. The methodologies, cost perspectives, and sources of cost data varied considerably among studies; with 13 studies took a top-down approach, and the rest including most of the U.S. studies used bottom-up approaches.…”
Section: Resultsmentioning
confidence: 99%
“…They will be used in a separate study to develop evidence-based recommendations for economic evaluations in spine surgery. Finally, a total of 130 clinical cost-effectiveness studies were included 24–153…”
Section: Resultsmentioning
confidence: 99%
“…We recommend public policies that implement universal health care coverage ( Kruk et al., 2018 ). Actually, the results of recent cost-effective studies suggest that surgery-related costs may be offset by a reduction in disability, and LMICs governments should be encouraged to conduct further spine trauma management and treatment cost-effectiveness analyses ( Lessing et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%